Game‐theoretic power allocation algorithm for downlink NOMA cellular system. Issue 25 (1st December 2019) - Aldebes, R.; Dimyati, K.; Hanafi, E.
Abstract : A new power allocation algorithm is proposed based on the Glicksberg game for cellular downlink non‐orthogonal multiple access (NOMA) networks. First, a price‐based user's utility function is proposed, and shown that it is effective and restrictive. Secondly, the Hessian matrix is used to derive an expression for power price based on the restricted transmission power and number of the served users in the cell. Then, the existence of a unique Nash equilibrium is proven and the optimum solution that maximises the utility function is presented. Finally, simulation results show that the proposed power allocation mechanism outperforms existing algorithms in terms of sum data rate and average data rate of the users.